Surface Structure of Aged Composite Insulator Studied by Slow Positron Beam - Peng, Xiangyang; Wang, Zheng; Lin, Hongsheng; Fang, Pengfei; Huang, Zhen (Journal of Wuhan University of Technology. Materials science edition, 2019)
Slow positron beam was applied to study the depth profile structure of the virgin and the aged high-temperature vulcanized silicone rubber (HTV). Scanning electron microscope (SEM) images show that the surface of virgin sample is smooth, while the outdoor aged samples are all rough. According to the S(E) curves obtained by slow positron beam, in a depth of more than 1 μm, the S parameter of the sample aged at low-potential side keeps the same value with the virgin one; while the S values of the highpotential side aged sample remain rather low in a depth of about 5 μm. Thermo gravimetric analysis (TGA) results show that the sample in high potential side contains more inorganic constituents than that of other samples. The results are attributed to the strong electric field induced corona aging at high potential side of the composite insulator.